Solanum lycopersicum L. VI005638 ... - GLIS Of The ITPGRFA (World Vegetable Center, 2022)
Plant Genetic Resource. Taxonomy: Solanum lycopersicum L. Common name(s): Tomato Other names: EANG SUB ARCTIC Conserved by: World Vegetable Center (WorldVeg), Chinese Taipei (Taiwan) Local sample unique identifier: VI005638 Method of creation: Acquisition Date: 1973-01-30 Other identifiers: n/a,L00231 Historical: No Biological status: Traditional cultivar/landrace MLS status: Included ...